If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 29 = 5 + -8(x + 6) Reorder the terms: 29 + 4x = 5 + -8(x + 6) Reorder the terms: 29 + 4x = 5 + -8(6 + x) 29 + 4x = 5 + (6 * -8 + x * -8) 29 + 4x = 5 + (-48 + -8x) Combine like terms: 5 + -48 = -43 29 + 4x = -43 + -8x Solving 29 + 4x = -43 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 29 + 4x + 8x = -43 + -8x + 8x Combine like terms: 4x + 8x = 12x 29 + 12x = -43 + -8x + 8x Combine like terms: -8x + 8x = 0 29 + 12x = -43 + 0 29 + 12x = -43 Add '-29' to each side of the equation. 29 + -29 + 12x = -43 + -29 Combine like terms: 29 + -29 = 0 0 + 12x = -43 + -29 12x = -43 + -29 Combine like terms: -43 + -29 = -72 12x = -72 Divide each side by '12'. x = -6 Simplifying x = -6
| 25x^2-36=o | | 6(5y-1)=-2y-38 | | 2+4r=5+4r | | X*7-4x=19-2x | | 90=-6(1+8q) | | 1-5m+3m=3 | | -x^3-6x^2+36x+216=0 | | -8-3(w+13)=4(w+11)-7w | | 15=5/6c | | -2(3x+1)-6x+7= | | 3x-2=55 | | 3/4(x-1)=7/4 | | (1-k)X^2-2(1+k)X+3(k+1)=0 | | 3[5x-2]+27=-24 | | 2v^2+11v-5=0 | | C=5/9(50-32) | | 8a-2=3a+5.5 | | 6x-8x+2x= | | 4x+x+(4x+6)+(4x+6)2=166 | | j/2+7=12 | | 200=16x-(3) | | x^2+3*x=97 | | 3/(2r-3)=.6 | | x^2+3x=97 | | 75=9x(7) | | 9(x-5)+4x=-7 | | 20-5x=6y+12 | | 555/x=11 | | -12=12v | | 3x+4+2x+5=24 | | 0.4/25 | | -9x-27=27 |